2019
DOI: 10.3390/ma12193114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe Addition on Microstructure and Mechanical Properties of As-cast Ti49Ni51 Alloy

Abstract: Effect of Fe addition on microstructure and mechanical properties of as-cast Ti49Ni51 alloy were investigated. The experimental results shows the microstructures of Ti48.5Ni51Fe0.5 and Ti48Ni51Fe1 alloys are mainly composed of TiNi matrix phase (body-centered cubic, BCC), Ti3Ni4 and Ni2.67Ti1.33 phases; the microstructure of Ti47Ni51Fe2 alloy is mainly composed of BCC TiNi, Ti3Ni4, Ni2.67Ti1.33, and Ni3Ti phases; the microstructure of the Ti45Ni51Fe4 alloy is mainly composed of TiNi, Ti3Ni4 and Ni3Ti phases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The µXRD results indicated that the Ni-Ti specimens possessed a polycrystalline texture with submicron grains. The XRD patterns showed that the homogenized sample was composed of a single phase of Ni-Ti matrix, and the other samples consisted of the Ni-Ti matrix and additional Ni-rich intermetallic phases, such as Ni 4 Ti 3, Ni 3 Ti 2, and Ni 3 Ti, which are consistent with previous literature [8,28,29]. As the duration of low-temperature aging is increased, Ni 4 Ti 3 phase was formed in the 10 min-aged samples, and Ni 3 Ti 2 and Ni 3 Ti phases were formed in the sample aged for over…”
Section: Crystal Structure Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…The µXRD results indicated that the Ni-Ti specimens possessed a polycrystalline texture with submicron grains. The XRD patterns showed that the homogenized sample was composed of a single phase of Ni-Ti matrix, and the other samples consisted of the Ni-Ti matrix and additional Ni-rich intermetallic phases, such as Ni 4 Ti 3, Ni 3 Ti 2, and Ni 3 Ti, which are consistent with previous literature [8,28,29]. As the duration of low-temperature aging is increased, Ni 4 Ti 3 phase was formed in the 10 min-aged samples, and Ni 3 Ti 2 and Ni 3 Ti phases were formed in the sample aged for over…”
Section: Crystal Structure Characterizationsupporting
confidence: 90%
“…It has been reported that precipitation hardening caused by the precipitation of Ni 4 Ti 3 produced by the age-hardening treatment contributes to the improvement of superelasticity by making the alloy less susceptible to slip [28]. These results revealed that it is important to control the microstructures and transformation temperatures to enhance superelasticity.…”
Section: Samples Cooling Processmentioning
confidence: 97%
“…An intermetallic compound can be formed because of the addition of Fe elements by replacing Ni atoms, resulting in a lattice distortion and atomic relaxation [19,20]. TiNiFe SMAs have good SMEs and mechanical properties and a relatively low martensitic transformation temperature [21], so they are also widely used in aerospace and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are three categories of the SMA that have been put into application [1], the Ni based, the Copper based and the stainless steel based. The Nibased SMA, especially the NiTi SMA shows excellent properties such as Shape Memory Effect and superelastic [2,3], damping characteristics [4,5], corrosion resistance [6][7][8] and biocompatibility [9,10]. Based on these characteristics, Ni-based SMA has been widely used in aerospace, machinery, chemical, electronics and medical fields [11][12][13].…”
Section: Introductionmentioning
confidence: 99%